Intra-household income inequality and preferences for redistribution - Tina Haußen (Friedrich Schiller University Jena, 2018)
We empirically analyze the relationship between income inequality and individual preferences for public redistribution, focusing on intra-household income inequality between spouses. Using data from the German Socio-Economic Panel, we find that both one's own earned income and earned intra-household income inequality are significantly negatively related to preferences for public redistribution. However, as the earned income inequality between partners increases, the poorer partner's preference for public redistribution declines while the richer partner's preference for public redistribution increases. The poorer partners' preferences may, in fact, indicate preferences for intra-household redistribution from the richer to the poorer partner. The richer partners' preferences may be explained by the fact that, when married, they can realize tax savings and, therefore, have to pay relatively less for public redistribution. Moreover, our results confirm previous findings regarding a partner's future social mobility prospects upon cohabitation ending, because they show that having a strong outside option, i.e., a high wage potential, is significantly negatively related to redistributive preferences, especially among those with an above-average future wage potential.
Keywords: D13; D31; D63; J12; H23; 330; redistributive preferences; intra-household income inequality; cohabitation; prospects of upward mobility